Dioctophyme renale (Goeze, 1782) (Nematoda: Dioctophymatidae) third-stage larvae in crab-eating raccoon (Procyon cancrivorus) and white-eared opossum (Didelphis albiventris) in southern Brazil - Rockenbach Portela, Priscila (2025)
Dioctophyme renale (Goeze, 1782) is a parasitic nematode that infects the kidneys of wild and domestic carnivores, including humans. The parasite is highly prevalent in southern Brazil, affecting a wide range of wild and domestic animals. While the high rates of parasitosis in stray and semi-domesticated dogs in the region are well documented, the dynamics of the parasite's life cycle and the intermediate (freshwater invertebrates) and definitive hosts are not completely known. This study aimed to report two new wild hosts for D. renale third-stage larvae in southern Brazil. The study was conducted in Capão do Leão, Rio Grande do Sul, Brazil. Three road-killed mammals, including one Procyon cancrivorus (G. Cuvier, 1798) and two Didelphis albiventris Lund, 1840, were collected and sent to the Federal University of Pelotas for parasitological analysis. The parasites were removed, cleaned, preserved, and identified based on morphological and morphometric characteristics. Third-stage larvae were found encysted in the serosa and gastric submucosa of D. albiventris (one host with 21 larvae and the other with 34 larvae) and in the stomach submucosa, liver parenchyma, and omentum of P. cancrivorus (infected with 3 larvae). This study reports, for the first time, natural infections of P. cancrivorus and D. albiventris by D. renale. Although adult parasites were not detected, the potential of these species to act as definitive or paratenic hosts cannot be dismissed. The findings support previous studies on larval migration involving the stomach and liver before reaching the peritoneal cavity. The study also highlights the relevance of dioctophymosis in the region, where environmental factors, stray dog populations, and interactions between wild and domestic animals may facilitate transmission. Overall, these findings enhance understanding of D. renale’s host range and underscore the need for continued surveillance in wild and urban environments in southern Brazil.